Determinan Anemia Ibu Hamil Trimester II dan III di Indonesia (Analisis Data Riset Kesehatan Dasar) - Pasmawati, Pasmawati; Hatma, Ratna Djuwita (Politeknik Kesehatan Tanjungkarang, 2019)
Anemia in pregnant women affects the occurrence of antepartum hemorrhage, postpartum hemorrhage, infection, obstacle to fetal growth and development, and prematurity. The aim of this study is to determine the determinants of anemia in second and third trimester pregnant women in Indonesia. The study is used secondary data of Basic Health Research year of 2013, a cross-sectional study design. The population of this study is pregnant women who were selected as respondents in the Basic Health Research year of 2013. The sample of this study consisted of 379 pregnant women, with a gestational age of 7-41 weeks. HB levels of pregnant women were examined using a portable Hemocue photometer. Independent variables is collected by interview. To determine the anemia determinant factors of pregnant women using Cox regression analysis. The results of this study show the prevalence of anemia in second and third trimester pregnant women in Indonesia is 41.2%. The factors that become anemia determinants in second and third trimester pregnant women in Indonesia are PR parity 1.42 (95% CI: 1.02-1.97), and ANC PR 1.65 (95% CI: 1.20-2,28). Pregnant women who carry out ANC according to standards can reduce the risk of anemia during pregnancy.